Análisis de las Estrategias de Marketing Digital Aplicadas por las Microempresas en el Sector Textil de las Provincia de Pichincha - Diaz Agila, Yadira Maribel (2018)
One of the most used channels of the media are the social networks, since it is a medium in which allow direct relations with the customers. The most of users spend more than half the time searching on internet, therefore, to be active in a social network is the best strategies that all enterprise can pose it. In our city, we have microenterprises that they give us textile products of good quality and it is of great benefits to fabricate according to necessities of customer, that’s why nowadays all microenterprises go to social networks, which makes that enterprises adapt to the world web creating strategies of value to satisfy the customers. On this investigation I proceeded to analyze the strategies of digital marketing that microenterprises doing to improve their positioning in the market, through its application I reached at the conclusion of how have been the change not only in the participation on markets, but also in form part of the great social networks. To be able to determine how much manage the social networks of the textile microenterprises, I developed an interview and proceeded to a brief analyze which allowed me to know if they are managing such social networks, which have been the benefits at use its and if they have gotten increases in their sales. KEY